Development Of A Streamline-Based Heat Transport Model For Thermal Oil-Recovery Simulation - Usman Usman; Norio Arihara (Testing Center for Oil and Gas LEMIGAS, 2005)
Fluid transport calculations based on streamlines have been used successfully for years to model two-phase in compressible flow simulations